Synthesis of 3(2)-phosphonylated thiazolo[3,2-a]oxopyrimidines - Kaskevich, Ksenia I.; Babushkina, Anastasia A.; Gurzhiy, Vladislav V.; Egorov, Dmitrij M.; Svintsitskaya, Nataly I.; Dogadina, Albina V. (Beilstein Journal of Organic Chemistry, 2020)
A series of 3(2)-phosphonylated thiazolo[3,2-a]oxopyrimidines was synthesized for the first time by the reactions of chloroethynylphosphonates with unsubstituted and 5(6)-substituted 2-thiouracils. The reaction of chloroethynylphosphonates with 6-substituted 2-thiouracils bearing electron-donor groups (CH3, Ph) proceeded with high regioselectivity involving the cyclization through the N3-nitrogen atom to form new 3-phosphonylated thiazolo[3,2-a]-5-oxopyrimidines with good yield. In the case of unsubstituted and 5-methyl-2-thiouracils, cyclization occurred predominantly through the N1 atom and partially via the N3-nitrogen atom to form a mixture of the corresponding thiazolo[3,2-a]-7- and 5-oxopyrimidines. A dramatic change in the reaction regioselectivity was observed in the case of 6-trifluoromethyl-2-thiouracil that afforded 2- and 3-phosphonylated 5-oxothiazolopyrimidines in a 1:1 ratio.
Keywords: chloroethynylphosphonate; heterocyclization; phosphonylated thiazolopyrimidines; phosphonylation; thiazolopyrimidine; 2-thiouracil